2009
DOI: 10.1088/0957-4484/20/41/415703
|View full text |Cite
|
Sign up to set email alerts
|

Superparamagnetic and ferromagnetic Ni nanorod arrays fabricated on Si substrates using electroless deposition

Abstract: The microstructures and magnetic properties of nickel nanorods fabricated using an anodic alumina oxide template and electroless deposition were investigated. The as-deposited nanorods were found to contain nanocrystalline grains with an average size of approximately 2-3 nm. The temperature-dependent magnetic hysteresis curves indicated superparamagnetic behavior of the as-deposited rods as a result of the reduction of ferromagnetic crystallites. The superparamagnetic (SM) Ni nanorods transformed into ferromag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 41 publications
(61 reference statements)
1
11
0
Order By: Relevance
“…16,17 The AAO was then removed, leaving the Ni rods to stand freely on Si. 18 The Ni/Si samples were post-annealed at 350 C for 15 and 30 min under atmospheric conditions to develop Ni-NiO core-shell structures with different NiO thicknesses. Meanwhile, two sets of Ni reference rods having the same dimensions as the Ni-NiO rods were prepared.…”
Section: Methodsmentioning
confidence: 99%
“…16,17 The AAO was then removed, leaving the Ni rods to stand freely on Si. 18 The Ni/Si samples were post-annealed at 350 C for 15 and 30 min under atmospheric conditions to develop Ni-NiO core-shell structures with different NiO thicknesses. Meanwhile, two sets of Ni reference rods having the same dimensions as the Ni-NiO rods were prepared.…”
Section: Methodsmentioning
confidence: 99%
“…Highly oriented Ni nano-arrays of diameter 70 nm and length 320 nm were fabricated directly onto Si substrates by electroless plating using an anodic aluminum oxide (AAO) template [12]. Prior to the electroless-deposition process, the AAO-Si sample was sensitized and activated by a SnCl 2 /HCl solution (40 g/L SnCl 2 þ3 ml/L HCl) and a PdCl 2 /HCl solution (0.15 g/L PdCl 2 þ 3 ml/L HCl).…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, the HRTEM demonstrated a polycrystalline structure for both the Ni-NiO and the reference Ni samples. Our previous work found that the as-deposited Ni featured a nano-crystalline structure [12], and a superparamagnetic (SM)-ferromagnetic phase transition of the arrays took place upon annealing. The conclusion was drawn that the magnetic transition is coupled to a microstructural modification that changes from nano-crystalline to polycrystalline phase [12].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies focused on the ferromagnetic metals such as Fe, Co, and Ni had shown that the basic magnetic properties could vary significantly as a function of both size and shape, especially, when those nanoparticles were distributed to the substrate of high specific surface area [4][5][6][7][8][9][10]. In this condition, for nanoparticles, the thermal agitation would weaken the interaction forces; prevent the existence of stable magnetization and lead to the superparamagnetic (SPM) state [11][12][13].…”
Section: Introductionmentioning
confidence: 99%